2013
DOI: 10.1073/pnas.1218219110
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB inhibitor targeted to activated endothelium demonstrates a critical role of endothelial NF-κB in immune-mediated diseases

Abstract: Activation of the nuclear transcription factor κB (NF-κB) regulates the expression of inflammatory genes crucially involved in the pathogenesis of inflammatory diseases. NF-κB governs the expression of adhesion molecules that play a pivotal role in leukocyteendothelium interactions. We uncovered the crucial role of NF-κB activation within endothelial cells in models of immune-mediated diseases using a "sneaking ligand construct" (SLC) selectively inhibiting NF-κB in the activated endothelium. The recombinant S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 44 publications
0
80
0
Order By: Relevance
“…However, these studies suggest that targeting the NF-κB in a cell- and pathway-specific manner could be beneficial in treating asthma. Consistent with this, selectively inhibiting NF-κB in endothelial cells in a murine models of peritonitis and rheumatoid arthritis has been shown to ameliorate both disease courses (113). These data together with the data in this manuscript, suggest that the NF-κB pathway can be selectively inhibited in a cell type- and activation stage-dependent manner (113).…”
Section: Discussionmentioning
confidence: 79%
“…However, these studies suggest that targeting the NF-κB in a cell- and pathway-specific manner could be beneficial in treating asthma. Consistent with this, selectively inhibiting NF-κB in endothelial cells in a murine models of peritonitis and rheumatoid arthritis has been shown to ameliorate both disease courses (113). These data together with the data in this manuscript, suggest that the NF-κB pathway can be selectively inhibited in a cell type- and activation stage-dependent manner (113).…”
Section: Discussionmentioning
confidence: 79%
“…In fact, most of the pro-inflammatory cytokines are associated with RA and are regulated by NF-κB (Tanaka et al 2014). The activation of this nuclear transcription factor pathway promotes an enhancement in the expression of adhesion molecules such as intracellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), E-selectin, and the increased release of chemokines and cytokines such as IL-1 and IL-8 (Sehnert et al 2013) Additionally, NF-κB is essential for the development and maturation of all hematopoietic cells including macrophage and neutrophils (Denk et al 2000). It is important to note that neutrophils are present in RA synovial fluid in the early disease stages, where they initiate and maintain joint inflammation, also, through NETosis, may release citrullinated autoantigens that are implicated in RA pathogenesis (Kaplan 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental animal model studies have demonstrated that inhibition of NF-B activation suppresses inflammatory responses (16,17). This transcription factor may also be involved in signaling increased Ca 2ϩ entry in ECs (9,18).…”
mentioning
confidence: 99%